Effects of dietary Jerusalem artichoke (Helianthus tuberosus) tuber powder and medium/long-chain fatty acids on production performance and fatty acid profile in laying hens - DAUKSIENE, AGILA; KLEMENTAVICIUTE, JOLITA; GRUZAUSKAS, ROMAS; KLUPSAITE, DOVILE; BARTKIENE, ELENA (The Indian Journal of Animal Sciences, 2020)
This study considers the use of Jerusalem artichoke (Helianthus tuberosus) tuber powder (HTT) and medium/ long-chain fatty acids (MLCFAs) in the nutrition of laying hens. A total of forty; 30-week-old laying hens were randomly distributed into four groups: control (C), 0.1% MLCFAs (T1), 2.0% HTT (T2), and both 0.1% MLCFAs and 2.0% HTT (T3). The fatty acid (FA) profile of eggs was analysed by gas chromatography, cholesterol by HPLC, and egg quality using a multifunctional automatic egg analyzer; production parameters of hens were also analysed. The results revealed that MLCFAs had a significant effect on accumulation of ô€„-linolenic acid (C18:3) and docosahexaenoic acid (C22:6) in egg yolk, but a higher impact on addition of HTT and MLCFAs was observed. Omega-3 FAs and omega-6/omega-3 FA ratio in egg yolk increased significantly on addition of MLCFAs alone or in combination with HTT. There were no significant effects of HTT and/or MLCFAs on body weight, feed intake, feed conversion ratio or egg mass output of laying hens. In addition, for HTT alone or in combination with MLCFAs, egg shell breaking strength was increased significantly (by 2%). A significant increase of Haugh unit was determined in the MLCFA group and in the HTT group. A significant decrease of cholesterol level was observed in all experimental groups. Supplementing laying hens' feed with HTT and MLCFAs facilitated the production of FAsenriched eggs. Slight effects of HTT and MLCFAs on egg quality, except Haugh unit, yolk cholesterol level and eggshell strength) and production performance of laying hens were observed.